Kepercayaan di Internet: Studi Kasus pada Korban Layanan Top Up Game Online di Media Sosial - Pratama, Gandi Aditya; Kusuma, Arif Surya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study aims to understand the characteristics of online game top-up fraud victims on social media, especially teenagers. Advances in technology and internet access have changed the way people seek entertainment, including online games, but have also triggered fraud in top-up transactions. This research identifies factors that make teenagers vulnerable to becoming victims, such as attractive promotions, many account followers, and low prices. Data was collected through observations and interviews with teenagers who have been victims of online game top-up scams. The results show that victims are generally teenagers aged 21 and under who are easily trusting, often find out about top-up services through social media such as Instagram, and tend to trust accounts recommended by friends or family. Promotional factors, number of followers, and low prices are the main drivers of transactions that lead to fraud. This research is expected to raise public awareness about the importance of vigilance in online transactions and provide insights for the development of fraud prevention strategies among teenagers.